Pengujian Karakteristik Usability pada Website Katalog Barang Menggunakan Pendekatan Black-Box Testing Berdasarkan Standar ISO/IEC 25010 - Agus Supriyanto; Bayu Aji; Ahmad Haidar; Indra Oktavian; Muhammad Nurfauzi Sahono (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2026)
The proliferation of catalog websites has increased demand for both attractive design and reliable software quality, yet many still suffer from malfunctioning features, unclear navigation, and slow response times. While ISO/IEC 25010 is widely used to evaluate software quality, usability testing on product catalog websitesparticularly through Black-Box Testing—remains underexplored compared to academic, government, or news portal websites. This study aims to test the usability characteristics of the Pina Official Store catalog website using a Black-Box Testing approach based on ISO/IEC 25010. Testing was conducted on 24 scenarios covering six usability sub-characteristics: Appropriateness Recognizability, Learnability, Operability, User Error Protection, User Interface Aesthetics, and Accessibility. Results show 19 of 24 scenarios (79.2%) met expected outcomes, categorized as